Identification of test liner paper production errors through six sigma DMAIC perception - Apriliyanto, Yohandika Tri; Muhaimin, Achmad; Shidik, Beta Arya Ash (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
To achieve normal quality, organizations must be able to be aware of and check factors that can affect product quality. Quality control aims to reduce the number of defective or damaged goods, ensure the final results provided comply with company quality guidelines. PT Lohdjinawi Widjaya is a company that produces paper in Indonesia, one of its products is test liner paper. This can be seen from production data for the last 4 days of August with total production of 953,625 kg and total defects of 35,084 kg. From the results of research and data processing using the Six Sigma DMAIC method, it can be concluded that the biggest defect in test liner paper products at PT. Lohdjinawi Widjaya total broken edge defects 18,400 kg or 52%, damaged cross-section 12,406 kg or %. The research results showed that the lowest Six Sigma level results were 3,55 on the fourth day and the highest on the first day was 4,08. Four factors influence product quality including materials, people, methods, and machine.